1993
DOI: 10.1016/0736-5748(93)90086-s
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β does not induce reactive astrogliosis, neovascularization or scar formation in the immature rat brain

Abstract: The adult mammalian central nervous system (CNS) reacts to a penetrating injury with the formation of a glial scar consisting of a newly formed glia limitans accessoria, basement membrane and meningeal fibroblasts. By contrast, in fetal and perinatal mammals a similar injury evokes only a reduced reactive astrogliosis, and a typical astroglial scar begins to develop only when the lesion has been placed beyond a critical developmental period. In the present investigation we have tested the hypothesis that IL-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Giulian et al (193) showed that IL-1b regulates astrocytic growth, and GM-CSF is a potent microglial mitogen that regulates microglial component of glial scars, suggesting that inflammation stimulates gliosis. Sievers et al (512), however, found that application of IL-1b does not induce reactive astrogliosis, neovascularization, or scar formation in immature rat brains. The glucocorticoid drug methylprednisolone (MP) is a potent anti-inflammatory drug that suppresses IL-1 expression.…”
Section: The Glial Scar Theorymentioning
confidence: 97%
“…Giulian et al (193) showed that IL-1b regulates astrocytic growth, and GM-CSF is a potent microglial mitogen that regulates microglial component of glial scars, suggesting that inflammation stimulates gliosis. Sievers et al (512), however, found that application of IL-1b does not induce reactive astrogliosis, neovascularization, or scar formation in immature rat brains. The glucocorticoid drug methylprednisolone (MP) is a potent anti-inflammatory drug that suppresses IL-1 expression.…”
Section: The Glial Scar Theorymentioning
confidence: 97%
“…First, the dose of IL-6 produced by the transgene at this age may be below the threshold needed to activate the cells. Second, the neonatal astrocyte might be function ally immature and unable to respond to the IL-6 [47][48][49]. Third, we analyzed total brain mRNA and therefore cannot rule out the possibility that there were small region-specific increases in the GFAP expression.…”
Section: Discussionmentioning
confidence: 99%
“…5,28,37 In immature animals, no astroglial scar forms due to the lack of a meningeal invasion. 3,5,6,16,39 This demonstrates the importance of meningeal cells for the formation of the glia limitans; it, however, leads to the question of why meningeal cells migrate into the lesion only in adult and not in immature animals. An understanding of the difference between the formation of the accessory and superficial glial membrane is of great interest since the establishment of a glial cicatrix is thought to be an impediment to regenerating axons, 19,35,36 and a comprehension of this process possibly allows one to interfere with cicatrization and provide regenerating axons with a more favorable environment.…”
mentioning
confidence: 99%